Studi Morfologi Pantai Rewata’a Desa Lalampanua - Rusdi Rusdi; Feri Padli; Hendra Hendra (Jambura Geoscience Review, 2020)
This research is aimed at knowing morphology characteristics and factors which influence landform that is located at Rewata’a Coastal. Geomorphology is a study stressed on landform characteristics with all processes and material at the world surface. The landform is seen as the appearance of landform as the main aspect of the landscape. The method used in this research is a qualitative descriptive method by collecting primary data, such as images or photos of land from that is directly taken from the research location. The phenomenological approach used to explain what, where, how, and why related to landform which based on available theory and prior research. The research result concludes that the Rewata’a Village morphology is cliffed coast, namely the coastal with the vertical cliff. Composed by host rock or hard sediment. Although we can find sand land at bay and north area. The landform found are delta, sea cave, beach, spit, notch, cliff, wave-cut platform, and stack.